Time-dependent effects of dexamethasone plasma concentrations on glucocorticoid receptor challenge tests. (July 2016) - Menke, Andreas; Arloth, Janine; Best, Johanna; Namendorf, Christian; Gerlach, Tamara; Czamara, Darina; Lucae, Susanne; Dunlop, Boadie W.; Crowe, Tanja Mletzko; Garlow, Steven J.; Nemeroff, Charles B.; Ritchie, James C.; et al.
Highlights: Plasma dexamethasone concentrations were measured in depressed patients of two independent cohorts using mass-spectrometry. Dex concentrations substantially influenced the readouts of the DST and dex-CRH test with an explained variance up to 41%. A case/control effect in the dex-CRH test was only apparent when controlling for dexamethasone concentrations. Dex concentrations at baseline and after treatment were highly correlated independent of treatment type and response status. Gene expression or cortisol concentrations measured 3 hours after dex ingestion were not influenced by dex concentrations. The incorporation of dex concentrations improves the assessment of endocrine dysfunction in depression. Abstract: Glucocorticoid challenge tests such as the dexamethasone suppression test (DST) and the combined dexamethasone/corticotropin-releasing hormone (dex-CRH) test are considered to be able to sensitively measure hypothalamic-pituitary-adrenal (HPA) axis activity in stress-related psychiatric and endocrine disorders. We used mass-spectrometry to assess the relationship of plasma dexamethasone concentrations and the outcome of these tests in two independent cohorts. Dexamethasone concentrations were measured after oral ingestion of 1.5 mg dexamethasone in two cohorts that underwent a standard (dexamethasone at 23:00 h) as well as modified (18:00 h) DST and dex-CRH test. The first study population was a case/control cohort of 105 depressed patients and 133 controls in which peripheral blood mRNA expression was also measured. The second was a cohort of 261 depressed patients that underwent a standard dex-CRH test at baseline and after 12 weeks' treatment with cognitive-behavioral therapy or antidepressants. Dexamethasone concentrations explained significant proportions of the variance in the DST in both the first (24.6%) and the second (5.2%) cohort. Dexamethasone concentrations explained a higher proportion of the variance in the dex-CRH test readouts, with 41.9% of the cortisol area under the curve (AUC) in the first sample and 24.7% in the second sample. In contrast to these strong effects at later time points, dexamethasone concentrations did not impact cortisol or ACTH concentrations or mRNA expression 3 hours after ingestion. In the second sample, dexamethasone concentrations at baseline and week 12 were highly correlated, independent of treatment type and response status. Importantly, a case/control effect in the Dex-CRH test was only apparent when controlling for dexamethasone concentrations. Our results suggest that the incorporation of plasma dexamethasone concentration or measures of earlier endocrine read-outs may help to improve the assessment of endocrine dysfunction in depression.